Light Path Modeling Based on Data Assimilation Using Changes in a Guided Light Passing Through a Packaged Optical Waveguide Device - Shizen Nakayama; Koichiro Ohkushi; Junpei Funatsuki; Tsuyoshi Konishi (IEEE Access)
This work demonstrates a method for light path modeling of various packaged optical waveguide devices in Si photonics and its applicability to inspection of the horizontal misalignments. The optical waveguide structure or light path is estimated by data assimilation using changes in a guided light passing through a packaged optical waveguide device. Tests of the method are carried out on the most essential structures such as straight, tapered, and inverse tapered structures with estimation errors less than a couple of percent in the simulation and it is experimentally verified using a straight Si waveguide (height: 220 nm, length: 6.9 mm, width: 440 nm) with a tapered optical coupling device (height: 220 nm, length: 2 mm) as a device under test. It is also expected to evaluate dynamical light path changes such as those due to thermal variation to verify that they affect the results in the device behavior after 3D co-packaging.